OVERCONFIDENCE AND FIRM VALUE (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Managerial overconfidence is an interesting topic to study.Overconfidence can be caused by the success of a company leader. Overconfidenceaffects the managerial actions and strategic policies taken by companies, especially ininvestment. This study aims to examine the effect of overconfidence calculated byusing capital expenditure and investment opportunity set calculated by using MarketBook Value Equity (MBVE) on firm value calculated by Tobin’sQ with capitalstructure as an intervening variable calculated by Debt to EquityRatio (DER). 232 openmanufacturing industries in Indonesia and 120 open manufacturing companies inMalaysia in the period of 2016-2019 were taken as the samples by using purposivesampling technique. In this study, the data were analyzed by using Eviews 10. Thisstudy confirms that there is an effect of overconfidence on firm value intervened by thecapital structure in open manufacturing industries in Indonesia and Malaysia.Meanwhile, the capital structure variable cannot intervene in the investmentopportunity set variable onthe firm value in open manufacturing industries in Indonesiaand Malaysia.